'Eye-opening': Case study of a documentary film series in a carceral setting. Issue 2 (3rd July 2022) - McVicar, Lindsay; Roy, Carole
Abstract: Adult education has a long tradition of engagement in social justice, but prisoners do not seem to garner much attention. This paper presents the findings of a case study of nine incarcerated women who attended a weekly screening of a documentary followed by a discussion for four weeks and individual interviews with all participants. Preliminary data analysis shows four main findings. First, participants appreciated non-formal learning and took pride in participating in discussions that were respectful of differences. Secondly, they expressed curiosity for new information and other perspectives. Thirdly, participants were inspired by stories of ordinary people facing adversity with perseverance and creativity. Finally, the carceral setting shaped their learning experience; although the films provided a break from the monotony of being imprisoned, the activity was nonetheless situated within the context of participants' correctional plans. As the numbers of incarcerated women in Canada continue to rise, these findings suggest that adult education has a role to play and that activities like this documentary series can offer stimulation and reflection to people who are incarcerated.